Socio-cultural issues in mathematics: A missing variable in Ghanaian basic school mathematics teacher preparation - Davis, Ernest Kofi (Journal of Educational Development and Practice, 2013)
Sociocultural practices of pupils and their teachers have been positioned in literature as being asset for meaningful learning of concepts generally (Hedegaard &. Chaiklin, 2005; Fleer & Robin, 2005) and mathematical concepts specifically (Prcsmeg, 2007). This paper draws on theories on the local aspect of mathematics, and teaching and learning to ascertain how the Ghanaian College of Education Mathematics curriculum deals with these aspects. The mathematics curricula at the colleges of Education in Ghana, the methods of teaching mathematics textbook and lessons from five experienced tutors of mathematics purposely selected from five Colleges of Education in Ghana constituted the main source of data. The documents were analysed qualitatively and presented as narrative description with illustrative examples. The study revealed among others that the College of Education Mathematics curriculum does not orient trainees to appreciate the local aspect of mathematics and mathematics pedagogy and recommends the need for curriculum developers to expose trainees to social and cultural issues in mathematics and mathematics pedagogy in order to make them better prepared as mathematics teachers.